Angiotensin-(1–7) Receptor Mas Deficiency Does Not Exacerbate Cardiac Atrophy Following High-Level Spinal Cord Injury in Mice - Järve, Anne; Qadri, Fatimunnisa; Todiras, Mihail; Schmolke, Shirley; Alenina, Natalia; Bader, Michael (Frontiers in Physiology, 2020)
Experimental spinal cord injury (SCI) causes a morphological and functional deterioration of the heart, in which the renin-angiotensin system (RAS) might play a role. The recently discovered non-canonical axis of RAS with angiotensin-(1-7) and its receptor Mas, which is associated with cardioprotection could be essential to prevent damage to the heart following SCI. We investigated the cardiac consequences of SCI and the role of Mas in female wild type (WT, n=22) and mice deficient of Mas (Mas-/-, n=25) which underwent spinal cord transection at thoracic level T4 (T4-Tx) or sham-operation by echocardiography (0, 7, 21 and 28 days post-SCI), histology and gene expression analysis at 1 or 2 months post-SCI. We found left ventricular mass reduction with preserved ejection fraction and fractional shortening in WT as well as Mas-/- mice. Cardiac output was reduced in Mas-/- mice, whereas stroke volume was reduced in WT T4-Tx mice. Echocardiographic indices did not differ between the genotypes. Smaller heart weight and smaller cardiomyocyte diameter at 1 month post-SCI compared to sham mice was independent of genotype. The muscle-specific E3 ubiquitin ligases Atrogin-1/MAFbx and MuRF1 were upregulated or showed a trend for upregulation in WT mice at 2 months post-SCI, respectively. Angiotensinogen gene expression was upregulated at 1 month post-SCI and angiotensin II receptor type 2 downregulated at 2 month post-SCI in Mas-/- mice. Mas was downregulated post-SCI. Cardiac atrophy following SCI, not exacerbated by lack of Mas, is a physiological reaction as there were no signs of cardiac pathology and dysfunction.